2006
DOI: 10.1128/jvi.00795-06
|View full text |Cite
|
Sign up to set email alerts
|

Altered Central Nervous System Gene Expression Caused by Congenitally Acquired Persistent Infection with Lymphocytic Choriomeningitis Virus

Abstract: Neonatal infection of most mouse strains with lymphocytic choriomeningitis virus (LCMV) leads to a life-long persistent infection characterized by high virus loads in the central nervous system (CNS) inInfection of the central nervous system (CNS) in humans by various DNA and RNA viruses can represent a severe health problem. Acute viral infections of the CNS frequently result in the destruction of specific neural cell populations as a direct consequence of virus multiplication or as a result of the host's ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 59 publications
4
39
0
1
Order By: Relevance
“…Mice develop diffuse viral infection both systemically as well as in the CNS, including productive and widespread neuronal infection (Rodriguez et al, 1983). The infection is not cytopathic, but mice nevertheless develop deficits in behavior and learning ability (Hotchin and Seegal, 1977;Kunz et al, 2006). Infection of the thymus results in the development of T-cell tolerance to LCMV and inability to clear the virus (Pircher , 1989).…”
Section: Small-animal Model Systemsmentioning
confidence: 99%
“…Mice develop diffuse viral infection both systemically as well as in the CNS, including productive and widespread neuronal infection (Rodriguez et al, 1983). The infection is not cytopathic, but mice nevertheless develop deficits in behavior and learning ability (Hotchin and Seegal, 1977;Kunz et al, 2006). Infection of the thymus results in the development of T-cell tolerance to LCMV and inability to clear the virus (Pircher , 1989).…”
Section: Small-animal Model Systemsmentioning
confidence: 99%
“…Expression of viral antigen is found in neurons localized in numerous regions of the brain including the neocortex, limbic system, hypothalamus, brain stem, thalamus, basal ganglia and the hippocampus -a region that is implicated in the development of memory and learning (104,106). Recently, it was shown that persistent viral infection is associated with alterations in the host gene profile of the brain (132). Most of the genetic perturbations were downstream of type 1 interferon (132) -a cytokine known to be systemically elevated in LCMV carrier mice (133,134).…”
Section: Behavioral Abnormalities In Carrier Micementioning
confidence: 99%
“…Specifically, persistently infected mice show reductions in spatial-temporal learning, assessed in a Y maze discriminated avoidance learning task, and decreases in explorative behavior in the context of novel environments (130)(131)(132). Expression of viral antigen is found in neurons localized in numerous regions of the brain including the neocortex, limbic system, hypothalamus, brain stem, thalamus, basal ganglia and the hippocampus -a region that is implicated in the development of memory and learning (104,106).…”
Section: Behavioral Abnormalities In Carrier Micementioning
confidence: 99%
See 1 more Smart Citation
“…15 Similarly, while the cellular targets of infection and the subsequent immune response have been extensively studied for LCMV, the virus remains a significant prenatal and postnatal threat and few effective treatments exist. 16,25,28,29 We hypothesize that a direct comparison of these two viruses during early infection of the neonatal CNS may help determine previously unidentified targets of infection, illuminate the neonatal host immune response following early infection, and clarify the mechanism of viral pathogenesis. The brains of 1-day-old CVB3 and LCMVinfected mice were analyzed for gene expression changes at 12,24, and 48 h post infection (PI) utilizing Illumina BeadArray Technology (MouseWG-6 v2 Expression Beadchips) in order to reveal the global neonatal host response for both neurotropic viral infections.…”
mentioning
confidence: 99%